2003
DOI: 10.1046/j.1439-0264.2003.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Anatomical and Histochemical Characteristics of the Lacrimal Glands in the American Bison and Cattle

Abstract: Dorsal lacrimal glands, superior glands of the third eyelid and Harderian glands (deep gland of the third eyelid) from 19 bison and 18 cattle free of apparent ocular disease were examined to compare the normal anatomical properties of these glands. All glands were characterized and measured (length and width). The gross anatomy of the dorsal lacrimal glands was similar, with the exception of a bipartite gland in cattle. The bison's superior gland of the third eyelid and Harderian gland was longer as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
22
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 13 publications
14
22
4
Order By: Relevance
“…It was also showed that there were no distinctions of the size and structure of the gland associated with sexual dimorphism. Similar results were obtained in the morphometric investigations of roe deer, American bison, cattle, and Iranian River buffalo [19,36,42]. The LG in examined alpacas, consistently with other research, was clearly divided into a lobes [2,36,42,43].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It was also showed that there were no distinctions of the size and structure of the gland associated with sexual dimorphism. Similar results were obtained in the morphometric investigations of roe deer, American bison, cattle, and Iranian River buffalo [19,36,42]. The LG in examined alpacas, consistently with other research, was clearly divided into a lobes [2,36,42,43].…”
Section: Discussionsupporting
confidence: 88%
“…It was elongate in shape and was light pink in colour. In gross appearance, it was an uniform, undivided gland, which was different than in Pinard et al [36] study. Pinard et al [36] showed that in American bison (Bison bison) and cattle the LG of both species were similar in appearance, with the exception of an accessory lobe in cattle.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations